Integração de sistemas de produção de biogás em estações de tratamento de esgotos com estratégia para a resiliência urbana em face às mudanças climáticas - Pereira, Brenda Natália (Universidade do Vale do Rio dos Sinos, 2025)
Population projections for 2054 estimate a total of 9.9 billion people worldwide, with more than half living in urban areas. This scenario poses challenges for urban infrastructure, requiring innovative and sustainable solutions to meet increasing demand in limited spaces. Wastewater Treatment Plants (WWTPs) play a key role in this context and, when using anaerobic processes, generate methane as a by-product. Methane has a global warming potential approximately 28 times greater than carbon dioxide, but it can be converted into thermal, electrical, mechanical energy, or vehicular fuel. The use of methane in WWTPs presents an opportunity for decentralized renewable energy generation, contributing to the reduction of greenhouse gas emissions, circular economy strategies, odor control, and the environmental and financial viability of these facilities. This study aimed to estimate the biogas generation potential of four WWTPs located in the state of Rio Grande do Sul, Brazil — Morada dos Eucaliptos (Novo Hamburgo), Vicentina (São Leopoldo), Tega (Caxias do Sul), and Serraria (Porto Alegre) — as well as to calculate the avoided emissions of greenhouse gases and the potential for electricity generation from methane. The results showed differences among the plants, with Serraria standing out for its highest specific methane production per kilogram of COD removed (0.232 m³ CH₄/kg COD) and the greatest energy generation potential (17,057.14 kWh/day). The Tega plant showed negative methane values due to the dilution of wastewater by the stormwater drainage system. The estimated avoided emissions revealed considerable reductions, especially at the Serraria plant, which could achieve a net reduction of over 51,000 tons of CO₂ equivalent per year. It is concluded that the energy recovery from methane can make WWTPs less dependent on the power grid and more capable of responding to extreme events and system instabilities, contributing to urban resilience and aligning with sustainability and climate adaptation goals.
Keywords: Biogás; Estação de tratamento de esgoto; Digestão anaeróbia; Resiliência urbana; Biogas; Wastewater treatment; Anaerobic digestion; Urban resilience; ACCNPQ::Engenharias::Engenharia Civil